2020
DOI: 10.1038/s41586-020-2194-z
|View full text |Cite|
|
Sign up to set email alerts
|

The wide-binary origin of (2014) MU69-like Kuiper belt contact binaries

Abstract: Following its flyby and first imaging the Pluto-Charon binary, the New Horizons spacecraft visited the Kuiper-Belt-Object (KBO) (486958) 2014 MU 69 (Arrokoth). Imaging showed MU 69 to be a contact-binary, made of two individual lobes connected by a narrow neck, rotating at low spin period (15.92 h), and having high obliquity (∼ 98 • ) 1 , similar to other KBO contact-binaries inferred through photometric observations 2 . The origin of such peculiar configurations is puzzling, and all scenarios suggested for th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Regardless of the way it formed, a low-mass proto-Arrokoth binary system would have to subsequently evolve into a contact binary. As discussed by Stern et al (2019), McKinnon et al (2020 and Grishin et al (2020), the binary system would have had to lose angular momentum in order for the components to come together. Proposed mechanisms include gas drag, the Kozai-Lidov mechanism, tidal evolution, and collisions.…”
Section: Origin Of Contact Binariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the way it formed, a low-mass proto-Arrokoth binary system would have to subsequently evolve into a contact binary. As discussed by Stern et al (2019), McKinnon et al (2020 and Grishin et al (2020), the binary system would have had to lose angular momentum in order for the components to come together. Proposed mechanisms include gas drag, the Kozai-Lidov mechanism, tidal evolution, and collisions.…”
Section: Origin Of Contact Binariesmentioning
confidence: 99%
“…The collisional origin of Arrokoth was then investigated further by McKinnon et al (2020), who showed that a low-velocity impact can indeed preserve the bi-lobate structure. Furthermore, Grishin et al (2020) demonstrated that dynamical evolution of an initially wide binary can lead to an Arrokoth forming gentle merger. As pointed out by Nesvorný et al (2018b) for the case of the comet 67P, Simon et al (2017) provided evidence that streaming instability may scale down to produce less massive <100 km objects.…”
Section: Origin Of Contact Binariesmentioning
confidence: 99%
“…2, the large lobe has higher oblateness as well as elongation than the small lobe. The large lobe had an oblateness ∼ 1.72× greater than that observed by Grishin et al (2020). The small lobe had an approximately equal oblateness of 0.1 to that observed by Grishin et al (2020).…”
Section: Elongation and Oblatenessmentioning
confidence: 58%
“…The large lobe had an oblateness ∼ 1.72× greater than that observed by Grishin et al (2020). The small lobe had an approximately equal oblateness of 0.1 to that observed by Grishin et al (2020). These authors used ellipsoidal models for the large and small lobes.…”
Section: Elongation and Oblatenessmentioning
confidence: 93%
See 1 more Smart Citation